Trinidad Constabulary on Parade - (:unkn) unknown (My University, 2009)
The police force line up on the day of parade.
Colour:Black and white;Style:Landscape;Bordered,Divided
Keywords: Postcards; Trinidad and Tobago; Police; Parades